3D kinematic analysis of diagonal stride in elite ski mountaineering (skialp) during worl cup races - Canclini, Ar.; Canclini, An.; Baroni, G.; Pozzo, R. (Science and Skiing VIII. Book of the 8th International Congress on Science and Skiing, 2020)
In recent years the ski mountaineering (SKIALP) has become more and more popular, and SKIALP skiers improved their technical and physiological performances. Due to the complex multiparametric environmental conditions (air and snow temperature, track, techniques, gradients, boots, ski) and the relatively recent development of the discipline, there is a lack of specific studies especially under race conditions. On the other hand, technical and physiological analysis comparing normal race and treadmill conditions have been undertaken (Canclini, 2007; Haselbacher et al., 2014; Tosi et al., 2009; Pozzo et al., 2016). The purpose of this study is to investigate the kinematics of elite skiers during high level competition.